ANALISIS KETERAMPILAN METAKOGNITIF PESERTA DIDIK KELAS V SD DALAM PEMBELAJARAN IPA: STUDI DI TIGA SEKOLAH DASAR KOTA SURABAYA - Suprayitno, Suprayitno; Rukmi, Asri Susetyo; Julianto, Julianto; Hidayati, Fitria (Primary School Teacher Education, Universitas Nahdlatul Ulama Sidoarjo, 2025)
Students metacognitive skills, including planning, monitoring, and evaluating the learning process, are essential in science (IPA) learning at the elementary level. However, these skills often receive insufficient attention due to the dominance of cognitively oriented instructional approaches. This study aims to analyze the metacognitive skills of fifth-grade students in science learning at three public elementary schools in Surabaya. A descriptive quantitative method was employed, supported by qualitative data from teacher interviews. The results indicate that students' skills in planning and evaluation are relatively well-developed, while difficulties persist in the monitoring aspect, particularly in maintaining reflective consistency and recalling prior material. Although teachers have implemented reflective and contextual approaches, passive learning habits remain a significant challenge. Based on these findings, it is recommended that science instruction place greater emphasis on explicit and structured strategies to foster students' thinking awareness in a sustainable manner, aligned with the principles of the Merdeka Curriculum.